HYDROGEL-BASED NANOCOMPOSITES OF THERAPEUTIC PROTEINS FOR TISSUE REPAIR - Zhu, Suwei (2014)
The ability to design artificial extracellular matrices as cell instructive scaffolds has opened the door to technologies capable of studying cell fates in vitro and to guide tissue repair in vivo. One main component of the design of artificial extracellular matrices is the incorporation of protein-based biochemical cues to guide cell phenotypes and multicellular organizations. However, promoting the long-term bioactivity, controlling the bioavailability and understanding how the physical presentations of these proteins impacts cellular fates are among the challenges of the field. Nanotechnolgy has advanced to meet the challenges of protein therapeutics. For example, the approaches to incorporating proteins into tissue repairing scaffolds have ranged from bulk encapsulations to smart nanodepots that protect proteins from degradations and allow opportunities for controlled release.